The Effect of Company Liquidity and Efficiency on Profitability in the Food and Beverage Sub-Sector on the Indonesia Stock Exchange - Rahmalia Utami; Ardhia Pramesti; Farah Margaretha Leon (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to identify variables that affect profitability in food and beverage companies listed on the Indonesia Stock Exchange. The addition of the quick ratio variable as an independent variable is a novelty in this study. Liquidity is measured by the current ratio, net working capital, and quick ratio while company efficiency is measured using total asset turnover. Profitability is measured by ROA and ROE. This study also includes control variables such as size, age, leverage ratio, and company growth rate to analyze the effect on profitability. This research method includes collecting data from 20 food and beverage companies over five years (2019-2023) with a total of 100 data that meet the criteria with the application of data processing analysis using panel data regression analysis techniques. The results of the study found that the current ratio has a significant positive effect on ROA and has no effect on ROE. Net working capital, company size, and growth rate do not affect ROA and ROE. Total asset turnover has a significant positive effect on ROA and ROE. The quick ratio and age have a significant negative effect on ROA and do not affect ROE. In addition, the debt ratio has a significant positive effect on ROE and does not affect ROA. This study confirms that the efficiency of asset use and liquidity management plays an important role in increasing the profitability of companies in the food and beverage sector, especially through the effect on ROA and ROE.